2011
DOI: 10.1002/lt.22328
|View full text |Cite
|
Sign up to set email alerts
|

Should we perform deceased donor liver transplantation after living donor liver transplantation has failed?

Abstract: By asking whether we should perform deceased donor liver transplantation (DDLT) after living donor liver transplantation (LDLT) has failed, we appear to be questioning the generally accepted current practice of retransplantation for transplant failure. However, we will also consider in this analysis that LDLT may have been performed for patients whose tumors were beyond the local criteria for listing or increased priority on the deceased donor (DD) wait list (ie, the patients were not eligible for DDLT origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…It has also demonstrated that with creative techniques for graft revascularization, excellent long‐term survival can be achieved, although with a price of considerable short‐term morbidity and re‐intervention. Right‐lobe liver retransplantation is justifiable not only because it saves lives; it lightens the bitter demand for deceased‐donor grafts and prevents retransplant candidates slipping from the elective surgery category into the urgent surgery category . Without doubt, liver transplant surgeons have to balance between fulfilling responsibilities to patients requiring retransplants and bringing risks to living graft donors.…”
Section: Discussionmentioning
confidence: 99%
“…It has also demonstrated that with creative techniques for graft revascularization, excellent long‐term survival can be achieved, although with a price of considerable short‐term morbidity and re‐intervention. Right‐lobe liver retransplantation is justifiable not only because it saves lives; it lightens the bitter demand for deceased‐donor grafts and prevents retransplant candidates slipping from the elective surgery category into the urgent surgery category . Without doubt, liver transplant surgeons have to balance between fulfilling responsibilities to patients requiring retransplants and bringing risks to living graft donors.…”
Section: Discussionmentioning
confidence: 99%
“…In patients transplanted for HCC from a living donor within regionally accepted criteria, re-transplantation for graft failure using a cadaveric liver is also possible and accepted by the scientific community. If the transplant from a living donor had been done over the criteria, re-transplant from a cadaver is not recommended [94][95][96][97][98].…”
Section: The Role Of Liver Transplant From Living Donormentioning
confidence: 99%
“…[22][23][24] They discussed ethical concerns with the double equipoise describing the balance between the recipient's survival benefit with or without LDLT and the risks of morbidity and mortality for the donor. Five years after the publication of the findings of the Vancouver forum, 25 it is well accepted that patients with HCC within the Milan criteria should be offered LDLT as a treatment option.…”
mentioning
confidence: 99%